(untitled) (Fiep Bulletin - online, 2014)
Obesity represents a public health problem at world level, with indiscriminate occurrence in the different age ranges and social-economic levels. For that reason, there is an urgent need that programs be developed with the intent of amending this preoccupying situation, hazardous to the individual and costly to the health systems; given that, the earliest they commence, the greater are the chances of success. Amid the factors which contribute to this situation in contemporaneous society, the co-relation between social-economic level and obesity has been under investigation. Hence, this study of bibliographic characteristic has seeked for data which could substantiate such affirmation related to the young population. For that matter, herewith are authors working on the subject amongst the lower and higher social-economic classes; and the results of the researches have linked overweight and child obesity to better social-economic conditions.